The Effect of Using Iron Slag as a Replacement for Fine Aggregates for Green Concrete Mixes - Alaa Abdeltawab Aboualelaa (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Green concrete is defined as a concrete which uses waste material as at least one of its components, or its production process does not lead to environmental destruction. The goal of sustainability is to maintain balance among economy, environment, and society, and to ensure that today’s needs are met without compromising the needs of future generations. This research studies the possibilities of using iron slag as total or partial replacement of fine aggregates to make green concrete. Compressive, tensile and flexural strength tests were conducted in by adding iron slag as replacement of sand in green concrete mixes in various percentages (10%, 20%, 40%, 60% , 80% ,100 at 7, 28 and 56 days. The results showed that the optimum percentage of Iron slag replacement is 60%.